Strategic Planning dalam Perspektif Teologi, Filsafat, Psikologi, dan Sosiologi Pendidikan - Agus Salim Chamidi (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2022)
This article tries to explain the strategic planning of education in the perspective of Islamic theology, philosophy of reconstructionism, social psychology, and structural-functional sociology. Articles based on library research. Strategic planning that relies on the work of leaders (managers) is the embryo of strategic management, and therefore this article tries to discuss it with the Wheelen-Hunger theoretical approach of strategic management and Ki Hajar Dewantara's trilogy of leadership. The result is that educational strategy planning requires a leader who is agile as well as civil servant.